Sedimentation in colloidal gels - Alharbi, Hessah (Kansas State University, 2021)
This study investigates the effect of stability ratio (W) on the sedimentation of colloidal gels. We monitored the temporal evolution of the gel height within our experimental time that lasted between 7-10 days. We found that some gels sediment while others do not. For sedimenting gels, the sedimentation height reaches an asymptotic value (Hₐ). In addition, we found that the temporal evolution of the sedimentation height profile depends on W in two manners. First, the characteristic time of the sedimentation height, t[subscript c], increases with decreasing W. In other words, the higher the W, the faster the sedimentation process. Second, we found that Hₐ decreases with increasing W.
Keywords: Sedimentation in colloidal gels; Colloidal gels; Sedimentation; Gel collapse; Stability ratio; Gel